Prevalence and risk factors of post-traumatic stress disorder symptoms among Chinese health care workers following the COVID-19 pandemic. Issue 4 (April 2023) - Li, Qi; Liu, Wei; Wang, Jie-Yu; Wang, Xiao-Guang; Hao, Bo; Hu, Yu-Bo; Deng, Xi; Liu, Lu; Zhao, Hu; Shi, Yan-Wei; Xue, Li
Abstract: In December 2019, coronavirus disease 2019 (COVID-19) appeared in Wuhan (Hubei, China) and subsequently swept the globe. In addition to the risk of infection, there is a strong possibility that post-traumatic stress disorder (PTSD) may be a secondary effect of the pandemic. Health care workers (HCWs) participating in the pandemic are highly exposed to and may bear the brunt out of stressful or traumatic events. In this cross-sectional study, we assessed the morbidity and risk factors of PTSD symptoms among Chinese HCWs. A total of 457 HCWs were recruited from March 15, 2020, to Mach 22, 2020, including HCWs in Wuhan and Hubei Province (excluding Wuhan), the areas first and most seriously impacted by COVID-19. The morbidity of PTSD symptoms was assessed by the Event Scale–Revised (IES-R). The risk factors for PTSD symptoms were explored by means of logistic regression analysis. Over 40% of the respondents experienced PTSD symptoms more than one month after the COVID-19 outbreak, and this proportion increased to 57.7% in Wuhan HCWs, especially females and HCWs on the frontline. Thus, rapid mental health assessment and effective psychological interventions need to be developed for frontline HCWs to prevent long-term PTSD-related disabilities. Moreover, Negative coping style and neuroticism personality may be regarded as high risk factors for PTSD symptoms. Improving individual coping strategies to enhance resilience should be the focus of further preventive intervention strategies.